Membentuk Kewarganegaraan Ekologis melalui Pendidikan Lingkungan berbasis Kegiatan Masyarakat - Edwin Nurdiansyah; Kokom Komalasari (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2023)
ABSTRACT This study aims to analyze the formation of the concept of ecological citizenship through community activity-based environmental education. This research was conducted in Talang Bubuk Village, Plaju District, Palembang City, South Sumatra Province. Data collection techniques were carried out through documentation and observation. Data analysis was performed using the Miles, Huberman & Saldana qualitative data analysis technique. Data analysis includes data reduction, data presentation and conclusion. The results of the study show that environmental education which is carried out on the basis of community activities is able to make people care more about the environment in which they live so that indirectly they have been able to form ecological citizenship in the community.